A Telemedicine Buprenorphine Clinic to Serve New York City: Initial Evaluation of the NYC Public Hospital System's Initiative to Expand Treatment Access During the COVID-19 Pandemic. Issue 1 (5th January 2022) - Tofighi, Babak; McNeely, Jennifer; Walzer, Dalia; Fansiwala, Kush; Demner, Adam; Chaudhury, Chloe S.; Subudhi, Ipsita; Schatz, Daniel; Reed, Timothy; Krawczyk, Noa
Abstract : Objectives: The purpose of this study was to assess the feasibility and clinical impact of telemedicine-based opioid treatment with buprenorphine-naloxone following the Coronavirus disease 2019 pandemic. Methods: Participants included in this retrospective analysis consisted of adult New York City residents with opioid use disorder eligible for enrollment in the NYC Health+Hospitals Virtual Buprenorphine Clinic between March and May 2020 (n = 78). Follow-up data were comprised of rates of retention in treatment at 2 months, referrals to community treatment, and induction-related events. Results: During the initial 9 weeks of clinic operations, the clinic inducted 78 patients on to buprenorphine-naloxone and completed 252 visits. Patient referrals included non-NYC Health + Hospitals (n = 22, 28.2%) and NYC Health + Hospitals healthcare providers (n = 17, 21.8%), homeless shelter staff (n = 13, 16.7%), and the NYC Health + Hospitals jail reentry program in Rikers Island (n = 11, 14.1%). At 8 weeks, 42 patients remained in care (53.8%), 21 were referred to a community treatment program (26.9%), and 15 were lost to follow-up (19.2%). No patients were terminated from care due to disruptive behavior or suspicions of diversion or misuse of Buprenorphine. Adverse clinical outcomes were uncommon and included persistent withdrawal symptoms (n = 8, 4.3%) and one nonfatal opioid overdose (0.5%). Conclusions: Telemedicine-based opioid treatment and unobserved home induction on buprenorphine-naloxone offers a safe and feasible approach to expand the reach of opioid use disorder treatment, primary care, and behavioral health for a highly vulnerable urban population during an unprecedented natural disaster.